The cattle of the tropics - Alemayehu, N. (Alemaya University of Agriculture, 1994)
Characterisation is important in genetic resources conservation and utilization. Data of 22,934 goats were collected by a rapid survey method to characterize goats of Eritrea, northern and western Ethiopia. Multivariate analyses were employed in the classification and the tracing of the ancestry of the indigenous goats. Eleven goat types were identified and described according to FAO standard descriptor lists, and three ancestral lines traced. Management practices and the performances of these goat types were also assessed. The observations indicated that: highlands of Ethiopia was centre of origin for most goat types identified; the primary base for diversity of the 11 goat types was agro-climatic variation, thus body size and others qualitative characters were significantly affected by climatic factors of the habitat where the particular goat type had adapted; human selection breeding had contributed to the phenotypic variation of goat types; large values of standard deviations in some of the measured variables for each goat type may indicate the existing potential of genotypic diversity. This could make the study region the gene pool of the goat genotypes.